Моделі оцінювання механізму управління підприємницькими структурами та стартап проєктами підприємств інтернет-торгівлі в умовах розвитку інноваційних цифрових технологій - Перерва, Петро Григорович; Кобєлєва, Тетяна Олександрівна; Копиця, Андрій Олегович (Дніпровський державний аграрно-економічний університет, 2026)
У статті здійснено системне дослідження моделей оцінювання механізму управління підприємницькими структурами та стартап-проєктами підприємств інтернет-торгівлі в умовах розвитку інноваційних цифрових технологій. Обгрунтовано необхідність модернізації класичних управлінських підходів з урахуванням специфіки електронної комерції, що характеризується високою динамікою, масштабованістю, залежністю від цифрових платформ та інтенсивною конкуренцією. Проаналізовано існуючі моделі оцінювання, визначено їхні переваги та обмеження. Запропоновано нові концептуальні моделі, які інтегрують фінансові, клієнтські, процесні, корпоративні та інноваційні аспекти управління. Особливу увагу приділено визначенню ключових показників ефективності, що забезпечують конкурентоспроможність, стійкість і гнучкість стартапів у цифровій економіці, а також їхню здатність до інноваційного розвитку, технологічної інтеграції та стратегічної адаптації. Розроблені моделі можуть бути використані як основа для розробки стратегій розвитку, оптимізації бізнес-процесів та підвищення конкурентоспроможності підприємницьких структур інтернет-торгівлі.

The article presents a comprehensive study of models for evaluating the management mechanism of entrepreneurial structures and startup projects of e-commerce enterprises in the context of innovative digital technology development. The modern economy is characterized by high dynamism, intense competition, and the constant impact of digital transformations, which necessitates the search for new approaches to managing entrepreneurial structures. Particular importance is attached to e-commerce, which acts as one of the key drivers of economic growth and innovative development, as it combines technological solutions, marketing tools, and entrepreneurial practices. The study substantiates the need to adapt classical management models to the specifics of online trade, which is distinguished by scalability, dependence on digital platforms, rapid updating of business models, and a high level of risk. Existing approaches to evaluating management effectiveness are analyzed, including startup life cycle models, investment attractiveness, customer value and loyalty, digital maturity of management, and innovative flexibility. Their advantages and limitations are identified, as well as opportunities for integration into the practice of e-commerce enterprises. A conceptual framework is proposed that combines financial, customer, process, and innovative aspects of management. This approach allows for a comprehensive evaluation of startup effectiveness, taking into account not only economic results but also the level of technological integration, the ability for innovative development, and strategic adaptation. Special attention is paid to defining key performance indicators, including conversion rate, average transaction value, repeat purchase rate, digital maturity index, innovative flexibility, and resilience to external risks. The article emphasizes that the development of innovative digital technologies creates new opportunities for managing entrepreneurial structures, particularly through the use of artificial intelligence, big data, business process automation, and omnichannel strategies. At the same time, it highlights the need to form a management system that ensures a balance between innovation and stability, enabling effective responses to the challenges of globalization and digital competition. The results of the study have practical significance for managers of e-commerce enterprises, investors, and startup developers, as they provide tools for comprehensive evaluation of management mechanisms. The proposed models can serve as a basis for developing growth strategies, optimizing business processes, and enhancing the competitiveness of entrepreneurial structures in the digital economy.
Models for evaluating the management mechanism of business structures and startup projects of online trading enterprises in the context of the development of innovative digital technologies
Keywords: управління; бізнес-процеси; підприємницькі структури; стартап-проєкти; цифрові технології; інформаційний потенціал; економічна оцінка; моделі; підприємства інтернет-торгівлі; конкурентоспроможність; management; business processes; entrepreneurial structures; startup projects; digital technologies; information potential; economic evaluation; models; e-commerce enterprises; competitiveness